Immunomodulatory activity of andrographolide on macrophage activation and specific antibody response - Wang Wei; Wang Jing; Dong Sheng-fu; Liu Chun-hong; Italiani Paola; Sun Shu-hui; Xu Jing; Boraschi Diana; Ma Shi-ping; Qu Di (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the immunomodulatory effects of andrographolide on both innate and adaptive immune responses. Methods: Andrographolide (10 μg/mL in vitro or 1 mg/kg in vivo) was used to modulate LPS-induced classical activated (M1) or IL-4-induced alternative activated (M2) macrophages in vitro and humor immune response to HBsAg in vivo. Cytokine gene expression profile (M1 vs M2) was measured by real-time PCR, IL-12/IL-10 level was detected by ELISA, and surface antigen expression was evaluated by flow cytometry, whereas phosphorylation level of ERK 1/2 and AKT was determined by Western blot. The level of anti-HBs antibodies in HBsAg immunized mice was detected by ELISA, and the number of HBsAg specific IL-4-producing splenocyte was enumerated by ELISPOT. Results: Andrographolide treatment in vitro attenuated either LPS or IL-4 induced macrophage activation, inhibited both M1 and M2 cytokines expression and decreased IL-12/IL-10 ratio (the ratio of M1/M2 polarization). Andrographolide down-regulated the expression of mannose receptor (CD206) in IL-4 induced macrophages and major histocompability complex/costimulatory molecules (MHC I, CD40, CD80, CD86) in LPS-induced macrophages. Correspondingly, anti-HBs antibody production and the number of IL-4-producing splenocytes were reduced by in vivo administration of andrographolide. Reduced phosphorylation levels of ERK1/2 and AKT were observed in macrophages treated with andrographolide. Conclusion: Andrographolide can modulate the innate and adaptive immune responses by regulating macrophage phenotypic polarization and Ag-specific antibody production. MAPK and PI3K signaling pathways may participate in the mechanisms of andrographolide regulating macrophage activation and polarization.